2020
DOI: 10.14507/epaa.28.5061
|View full text |Cite
|
Sign up to set email alerts
|

Modos de ideologia e de colonialidade em materiais didáticos de Contabilidade

Abstract: This paper aims to identify aspects of neoliberal ideology in the chapters dealing with accounting principles, in the textbook Introductory Accounting by FEA USP and in CPC00 (R2) - Conceptual Framework for Financial Reporting. To achieve the objective, we analyze the typical linguistic modes through which ideology operates, based on Thompson (2011). It is a critical and interpretative research that aims to discuss accounting education in Brazil from a decolonial perspective. The analyzed texts identified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(80 reference statements)
0
2
0
1
Order By: Relevance
“…Stenka & Jaworska, (2019) utiliza a ECD investigar a existência de usuários fictícios nas consultas públicas do IASB, observando os processos de naturalização dos discursos que sustentam determinadas posição sociais. As investigações de Ferguson et al (2009), Mendes et. al.…”
Section: Estudos Críticos Do Discursounclassified
See 1 more Smart Citation
“…Stenka & Jaworska, (2019) utiliza a ECD investigar a existência de usuários fictícios nas consultas públicas do IASB, observando os processos de naturalização dos discursos que sustentam determinadas posição sociais. As investigações de Ferguson et al (2009), Mendes et. al.…”
Section: Estudos Críticos Do Discursounclassified
“…),Ejiogu et al (2021),Zhang e Andrew (2014, e que foram revelados pelas categorias analíticas da intertextualidade e interdiscursividade. A hegemonia do órgão, molda as estruturas e práticas sociais com implicações na formação dos indivíduos, conforme apontamMendes, Fonseca & Sauerbronn (2020).…”
unclassified
“…In accounting education, Mendes, Fonseca, and Sauerbronn (2020) analyzed, through a decolonial lens, aspects of neoliberal ideology in the chapters dealing with accounting principles in the book Contabilidade introdutória (Introductory accounting), written by faculty of the School of Economics and Administration at the University of São Paulo. The book is widely used in several basic training courses in Brazil.…”
Section: Contributions From Decolonial Contributions From Decolonial ...mentioning
confidence: 99%
“…The book is widely used in several basic training courses in Brazil. Mendes et al (2020) indicated the need for an educational accounting policy that challenges traditional calculations and techniques, recognizing the role of accounting as a language with its own grammar and structure that ensure the reproduction of neoliberal practices in Brazil.…”
Section: Contributions From Decolonial Contributions From Decolonial ...mentioning
confidence: 99%
“…Com auxílio do software R Studio (Aria & Cuccurullo, 2017), para análise desses dados, foi possível visualizar um crescimento médio de publicações referindo-se a esse termo após o ano de 2012. Ademais, nos estudos com foco no processo de ensino-aprendizagem do componente curricular de Contabilidade Introdutória é encontrada a abordagem de tópicos como: (i) métodos de ensino, estratégias de aprendizado e desempenho acadêmico (Cunha et al, 2013;Nogueira, 2012;Rezende et al, 2016;Santos & Costa, 2019;Sena & Sallaberry, 2021;Vellani & Maciel, 2011;Vendramin & Araujo, 2020); (ii) educação superior e currículo (Bianchi et al, 2010;Caria et al, 2016;Hofer et al, 2005;Mendes et al, 2020;Raimundini et al, 2009;Soares et al, 2012); (iii) mercado de trabalho e desenvolvimento de competências e habilidades (Slomski et al, 2010); e, (iv) metodologias ativas e o uso de tecnologias educacionais (Costa et al, 2020;Nogueira & Casa Nova, 2013;Quintana & Afonso, 2018;Rocha Neto & Leal, 2020). Todavia, é notável que uma parte significativa das pesquisas sobre a Contabilidade Introdutória está baseada na percepção dos estudantes.…”
Section: Justificativas Lacuna E Contribuiçõesunclassified